Optimization of Wear Process Parameters of Al6061-Zircon Composites Using Taguchi Method - R. Vijayakumar; J. S. Srikantamurthy; Shanawaz Patil; S. Rudresha; A. Manjunatha; T. Hemanth Raju; A. Haiter Lenin (Advances in Materials Science and Engineering)
Aluminium metal matrix composites are utilised extensively in a variety of engineering applications, including those involving automobiles, aerospace, and other fields of engineering because of its superior tribological properties. In the present research work, an effort was made to investigate the wear behaviour of an aluminium alloy called Al6061 that was manufactured by a process called two-step stir casting. The alloy was strengthened with zircon particles. The zircon particles were varied in three different percentages: six percent, nine percent, and twelve percent. A pin-on-disc wear testing machine was used to investigate the wear behaviour of Al6061-Zircon composites at elevated temperature 100°C. Experiments were performed as per the design of the experiments that had been generated using Taguchi’s method. In order to do the analysis on the data, L27 Orthogonal array was chosen. During the wear process, an investigation was conducted to determine the impact of applied load, speed, percentage of reinforcement, and sliding distance on the wear response parameter. An analysis of variance (ANOVA) table and a regression equation were established to facilitate this study. In order to conduct the study of the dry sliding wear resistance, the aim of this equation was to select the smallest possible features. The scanning electron micrographs of Al6061-Zircon composites show the presence of zircon particles. It also shows that the particles are distributed uniformly in the Al6061 matrix. The scanning micrographs of worn out surfaces of Al6061-Zircon composites show the presence of grooves on the wear surface moving parallel to the sliding direction. According to the outcomes, the factor with the major impact is the load, followed by speed, sliding distance, and the percentage of reinforcement. In conclusion, confirmation tests were conducted in order to validate the experimental results.